Voice onset time and beyond: Exploring laryngeal contrast in 19 languages. (January 2019) - Cho, Taehong; Whalen, D.H.; Docherty, Gerard
Highlights: This collection marks 50 years of research on VOT and the voicing contrast in the world's languages. Nineteen languages are studied in 11 papers based on data obtained from over 270 speakers. VOT continues to be a useful first estimate of laryngeal contrast in voicing across languages. Multi-dimensional approaches are needed to understand the nature of voicing contrast. Universals and variation and articulatory underpinnings of voicing contrast are discussed. Abstract: In this special collection entitled Marking 50 Years of Research on Voice Onset Time and the Voicing Contrast in the World's Languages, we have compiled eleven studies investigating the voicing contrast in 19 languages. The collection provides extensive data obtained from 270 speakers across those languages, examining VOT and other acoustic, aerodynamic and articulatory measures. The languages studied may be divided into four groups: 'aspirating' languages with a two-way contrast (English, three varieties of German); 'true voicing' languages with a two-way contrast (Russian, Turkish, Brazilian Portuguese, two Iranian languages Pashto and Wakhi); languages with a three-way contrast (Thai, Vietnamese, Khmer, Yerevan Armenia, three Indo-Aryan languages, Dawoodi, Punjabi and Shina, and Burushaki); and Indo-Aryan languages with a more than three-way contrast (Jangli and Urdu with a four-way contrast, and Sindhi and Siraiki with a five-way contrast). We discuss the cross-linguistic data, focusing on how much VOT alone tells us about the voicing contrast in these languages, and what other phonetic dimensions (such as consonant-induced F0 and voice quality) are needed for a complete understanding of laryngeal contrast in these languages. Implications for various issues emerge: universal phonetic feature systems, effects of language contact on linguistic levelling, and the relation between laryngeal contrast and supralaryngeal articulation. The cross-linguistic VOT data also lead us to discuss how the distribution of VOT as measured acoustically may allow us to infer the underlying articulation and how it might be approached in gestural phonologies. The discussion on these multiple issues sparks new questions to be resolved, and provide indications of where the field may be best directed in exploring laryngeal contrast in voicing in the world's languages.